Human-Centered Software Engineering Software Engineering Models, Patterns and Architectures for HCI - Seffah, Ahmed; Vanderdonckt, Jean; Desmarais, Michel C. (Human-Computer Interaction Series, 2009)
The fields of Human-Computer Interaction (HCI) and Software Engineering (SE) have evolved almost independently from each other until the last two decades, when it became obvious that an integrated perspective would benefit the development of interactive software applications as considered in both disciplines. The chapters in this book are written by prominent researchers and practitioners who bring to light the major issues and challenges posed by this integration, and offer a variety of solutions in order to address the integration of HCI and SE, including: • Extensions of software development methodologies to accomodate for the specific constraints of usage-centered design. • Introduction of innovative, structured, and model-driven user interface engineering approaches. • Addressing software architecture issues in the design of user interfaces. • Reingineering of existing systems for better usability.